Safety Assessment of TENORM Waste Landfill on Bangka Island Using Resrad Offsite 4.0 - Setiawan, A.; Kurniati, M.; Iskandar, D.; Sucipta, S; Pratama, H. A.; Setiawan, R. (Atom Indonesia, 2025)
Bangka Island faced serious environmental challenges due to TENORM (Technologically Enhanced Naturally Occurring Radioactive Materials) waste from tin mining activities. The waste contained radionuclides such as U-238, Th-232, and K-40, which could have had detrimental effects on human health and the environment. To solve this problem, TENORM waste should be disposed of in the class II landfill facility. The Class II landfill was more efficient by cost than the Class I landfill. The landfill design provide a waste contamination layer with dimensions of 160 × 160 × 3 meters. This landfill class has 5 layers from top to bottom cover layers such as the contamination or waste layer, protective coating layer, layer for collecting and transferring, geomembrane layer, soil barrier layer, leak detection system layer, and base layer, which each layer was intended to safeguard against contamination. These protective layers were required to adhere to precise specifications regarding material, thickness, and hydraulic conductivity to effectively manage waste and leachate. Additionally, the base layer consisted of compacted clay, designed to regulate hydraulic conductivity and offer sustained environmental protection. This paper will discuss the radiological safety assessment of this landfill design. This design was modeled using Resrad Offsite 4.0 software to assess its radiation safety in order to fulfill landfill safety requirements. The simulation results showed a maximum radiation dose of 0.40537 mSv per year at a distance of 200 meters from the landfill center, which was estimated to persist for 29,265 years after the landfill was closed. The cancer risk probability was estimated to be 4.25 × 10⁻⁴. More importantly, this dose was still below the safe limit set by BAPETEN (Nuclear Energy Regulatory Agency) for public radiation exposure, which is 1 mSv per year. The class II landfill design, based on the simulation results, was safe for public health and the environment.